EKSISTENSI PEREMPUAN DALAM NOVEL PENGAKUAN EKS PARASIT LAJANG KARYA AYU UTAMI - , RAHMAT SULHAN HARDI, Dr. Wening Udasmoro, M.Hum. DEA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The material object of this study is novel with tittle: Pengakuan: Eks Parasit Lajang (Admission: Ex Single Parasite) written by Ayu Utami. The formal object of the study is the woman existence. The novel tale on figure A who oppose a myths that make a limitation for woman freedom. That myths among others are virginity myth, elder virgin, the creation of woman from Adam rib bone. The objectives of the study were: 1) to describe the way the woman treating their body as an embody of their existence, 2) describe the way the woman find and defend their existence, and 3) expressing the message of the author. These problems were studied by existentialism theory by Jean-Paul Sartre who viewed a woman as a free human. The result of this study showed that the author presented a woman image whose have existence. She presented figure A who able to overcome the world wherein there were myths that were born from the family rule, custom and religion teaching, that disadvantaged a woman. That myths were the condition that were faced by a woman in their effort to be existence human. A was depicted as a woman who able to overcome that facticity because she was lived in the condition of être pour-soi who in awareness of freedom and responsibility on their choice and defended their existence by their choices in faced that conditions. Whereas the woman would fall into être en-soi and existed in mauvoise foi if they choose to defer to the facticity and put off their freedom as freedom human